Influencer Narrative Communication in Promoting Skaye Cafe Lampung to Potential Visitors: A Study of Instagram Reels Content on the @aqillaaqtrn Account - Agnes Monica Herwan; M Denu Poyo; Noning Vera Wati (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the forms of narrative communication used by an influencer in promoting Skaye Cafe Lampung to potential visitors through Instagram Reels. The research employed a qualitative descriptive approach with a post-positivist paradigm. Data were collected through non-participant observation of five Instagram Reels uploaded on the @aqillaaqtrn account, in-depth interviews with key and supporting informants, and documentation. The findings indicate that the influencer applied three forms of narrative communication: experience-based narratives, value-based narratives, and accessibility-based narratives. Experience-based narratives highlighted the atmosphere, facilities, and social experiences at the café. Value-based narratives emphasized promotional offers, affordable prices, and product benefits to attract potential visitors. Accessibility-based narratives focused on the convenience of ordering through online food delivery services. These narrative forms were presented through storytelling that combined visual elements, personal experiences, and persuasive messages, making the promotional content more engaging and relatable. The study concludes that integrating these forms of narrative communication enables influencers to deliver promotional messages more effectively and enhance potential visitors' interest in Skaye Cafe Lampung.